Strategic Planning for Improving the Quality of Facilities and Infrastructure in Madrasas - Zefliani, Zella; Fauzan, Ahmad; Amiruddin, Amiruddin; Ayu, Sovia Mas; Junaidah, Junaidah (Universitas Islam Negeri Raden Intan Lampung, 2023)
The research discusses the implementation of educational programming (strategic planning) that has been established as a guide in an effort to provide clarity of direction for each activity, so that each activity can be pursued and carried out as efficiently and effectively as possible to maintain the quality of the institution. This research aims to find out how the formulation of vision and mission, analysis of internal and external environment, analysis of strategy options and key success factors, and the determination of goals, objectives and strategies at MTs Negeri 1 Martapura. The research is a field research, with the nature of research in the form of qualitative descriptive methods. In collecting data, the author uses the methods of interview, observation, and documentation. The source of data is the head of the madrasa, the deputy head of the facilities and infrastructure section, the head of administration. Then the data that has been collected is analysed using the stages of data reduction, data presentation and conclusion drawing. Based on the results of the research that the author has done, the strategic planning stage at MTs Negeri 1 Martapura OKU Timur has been carried out well. The process of formulating the vision and mission fulfils the criteria for a good vision and mission according to Sedarmarmayanti's theory. Analysis of the internal and external environment has been carried out and produces information about the strengths, weaknesses, opportunities and threats of the madrasa, analysis of strategic choices and key success factors has been carried out and continues to be pursued to be even better, the madrasa has also obtained goals and objectives.